Impact of world oil prices on an energy exporting economy including monetary policy - Victoriia Alekhina; Naoyuki Yoshino (Asian Development Bank Institute (ADBI), 2018)
This research investigates the interrelationship between the main macroeconomic indicators of an oil exporting country and world oil prices using a vector autoregressive (VAR) approach. We focus on an economy, which is a non-OPEC oil exporter and its oil revenues account for a significant proportion of the country's total export and budget revenues. We explain the oil price transition mechanisms to this economy from the export side and through the fiscal channel taking into account the monetary policy factor. The results suggest that oil price fluctuations have a significant impact on the oil exporting country's real GDP, CPI inflation rate, interest rate, and exchange rate. Moreover, to estimate monetary policy rule for this energy exporter, we test the Taylor equation and associated Taylor rule, including the oil prices gap, since the latter may have a significant impact on the key policy rate. The evidence suggests that the Taylor rule describes the post-financial crisis monetary policy of this economy relatively well. Finally, we discuss future research and lessons from this economy for monetary policy makers.
Keywords: Q41; Q43; Q48; 330; oil prices; energy exporters; macro-economy; VAR model